Avaliação da força, estresse muscular e marcadores inflamatórios de indivíduos com doença pulmonar obstrutiva crônica submetidos a treinamento resistido com tubos elásticos - Silva, Bruna Spolador de Alencar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is known that physical exercise is effective in the rehabilitation process of patients with chronic obstructive pulmonary disease (COPD), but the behavior of functional variables and inflammatory expression from resistance training with elastic tubing are not yet clear in the literature in these patients. Objective: To evaluate the strength, functional capacity, muscle stress and inflammatory expression between a resistance training performed with elastic tubing and weight machines in pacients with COPD. Methods: We evaluated 19 patients with COPD randomized into 2 groups: resistance training with elastic tubing (GR1: n: 9) and resistance training with weight machines (GR2: n: 10). The training was performed 3 times weekly for 12 weeks, with initial intensity of 2x15 RM progressive to 4x6RM. Initially we performed initial assessment and evaluation of lung function.The measurement of muscle strength test were performed using a digital dynamometer; blood sampling for analysis of expression of inflammatory TNF-α, IL-6 and PAI-I and the metabolic variables glucose, triacylglycerol (TAG) and total cholesterol were performed at baseline, 6 weeks and 12 weeks (48 hours after the last training session); the functional capacity was done through the Six-minute walk test (6MWT) (baseline and 12 weeks) and the muscle stress through the measurement of creatine kinase (CK) (baseline, 24, 48 and 72 hours after protocol) Results: There were significant gains in muscle strength and functional capacity in both groups, with similar gain deltas. Significant peak in CK levels was observed 24 hours after the end of training on the GR2 (p = 0.027), but with value within the normal range...

É conhecido que o exercício físico é eficaz no processo de reabilitação de pacientes com doença pulmonar obstrutiva crônica (DPOC), porém o comportamento de variáveis funcionais e expressão inflamatória a partir de treinamento resistido com tubos elásticos com estes pacientes ainda não estão claros na literatura. Objetivos: Avaliar o comportamento da força, capacidade funcional, estresse muscular e expressão inflamatória entre um treinamento resistido realizado com tubos elásticos e em aparelhos de musculação em indivíduos com DPOC. Métodos: Foram avaliados 19 pacientes com DPOC, randomizados em dois grupos: treinamento resistido com tubos elásticos (GR1:n:9) e treinamento resistido com aparelhos de musculação (GR2:n:10). O treinamento foi realizado três vezes semana durante 12 semanas, com intensidade inicial de 2x15 repetições máximas(RM) progressiva até 4x6RM. Inicialmente foi realizada avaliação inicial e avaliação da função pulmonar. A mensuração da força muscular foi realizada por meio de dinamômetro digital; as coletas sanguíneas para análise da expressão inflamatória de TNF-α, IL-6 e PAI-I e das variáveis metabólicas glicose, triacilglicerol (TAG) e colesterol total foram realizadas nos momentos basal, seis semanas e 12 semanas ( 48 horas após a ultima sessão de treinamento); a capacidade funcional foi realizada por meio do Teste de Caminhada de Seis minutos (TC6) (basal e 12 semanas)e o estresse muscular por meio da mensuração de creatina quinase (CK) (basal, 24, 48 e 72 horas após protocolo) Resultados:Houveram ganhos significativos de força muscular e capacidade funcional em ambos os grupos, com ganhos relativos semelhantes...
Keywords: Fisioterapia; Educação fisica; Aptidão física; Creatina-quinase; Miosite; Pneumopatias obstrutivas; Physical therapy